TINJAUAN KONDISI FISIK ATLET SEPAKBOLA PELATCAB KOTA PEKANBARU - Rizki Andrian; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack:This research is descriptive research, which aims to determine the physical condition (bleep test) football athlete pelatcab city of Pekanbaru. Problems that occur in the athlete both in matches and training him among them are the lack of fighting spirit and athletes both in training and matches it caused a lot of athletes who mangalami fatigue or tiredness that is not playing, not optimal technique is done in because of fatigue which naturally like, passing unfocused, shhoting are weak, lost the ball when dribbling, ball control that is less than the maximum, it is presumably because the element is not optimal endurance athletes. The purpose of this study was to assess the physical condition of athletes football pelatcab Pekanbaru city with regard to aerobic endurance or VO2Max.Populasi in this study were all athletes who totaled 18 people. Data were collected by conducting bleep test or MFT. Based on data analysis aerobic endurance or VO2max, the average owned by football athletes Pekanbaru city pelatcab 34-42 categorized enoughKeywords : Physical conditions, Athletes Football